Complexity and Narrow Bracketing in Credit Choice - Kenan Kalaycı; Marta Serra-Garcia (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
We examine experimentally the effect of complexity on individual decision making. We focus on credit choices, as they have been widely criticized for their complexity in recent years. In a first study, we find that complexity in benefits leads to random mistakes, while complexity in costs leads to a specific mistake: choosing a high-benefit loan, with very costly repayment schemes. In a second study, we show that individuals still (mistakenly) choose the high-benefit loan, even if cheaper and simple loans are available. This suggests that, when costs are complex, individuals bracket narrowly, focus on benefits and ignore costs, while they do not when benefits are complex. Hence, our results show that complexity and narrow bracketing may be deeply intertwined: complexity that makes narrow bracketing cognitively easier is likely to lead to myopic choices, such as choosing complex and expensive loans, despite the presence of simple and cheaper loans.
urn:nbn:de:bvb:19-epub-13035-4
Keywords: C91; D03; D14; G02; 330; Complexity; Credit; Mistakes; Narrow Bracketing; Kredit; Konsumentenverhalten; Komplexitätsmanagement; Verhaltensökonomik; Test